SOCIAL PHARMACY INITIATION TO IMPROVE QUALITY OF LIFE AND HEALTH EDUCATION IN FISHERMAN VILLAGE KAMAL MUARA - Vardhani, Afifah Kusuma; Radji, Maksum; Syarafina, Nihla Nurin; Maisaroh, Siti; Amalia, Yayu; Ayuningtyas, Yessy Tri; Belladona, Ladisa Virgiane; Aintania, Rasyya; Putri, Andi Rani Anggraini; Mentari, Claudia; Afrilia, Salsa; Hartanto, Virgo Budi (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Kamal Muara Sub-district, Penjaringan District, located in the coastal area of ​​North Jakarta, is a community with a heterogeneous population in terms of ethnicity, culture, and occupation. Most of the residents work as fishermen and factory workers. Various health and environmental issues such as low awareness of personal hygiene and healthy eating habits were problems faced by coastal residents. This activity aims to provide health education, improve nutrition, and raise environmental awareness through a social pharmacy practice program. The methods used in this program are observation and field practice. The students participated in activities such as education on safe drug use, healthy exercise sessions, creative healthy fish cooking, recycling workshops, proper handwashing and tooth brushing techniques, and environmental cleaning. The results of this study show that awareness and knowledge of the importance of health in the community increased through a series of educational programs. The program also successfully promoted collaboration and mutual cooperation among residents with significant support from community leaders and academia. The positive impact of this program is expected to last and become part of the daily habits of the community.